Evaluation on the Impact of Motivation on Employee Performance: An Assessment of Timber Milling Industry in Zimbabwe - Mlambo, Aleck (European Journal of Applied Sciences, 2024)
Motivation is considered as the force that drives employees towards attaining specific goals. The main purpose of this study was to establish the impact of motivation on employee performance and discuss the factors that motivate employees in the organisation. The study was prompted by low performance by employees, failure to address motivational factors, failure to establish the benefits of motivation in the organisation and how motivation impact on performance. The main objective of the study was toestablish the impact of motivation on employee performance and the effect of motivation on employees. The mixed methods research, which is a combination of quantitative and qualitative approaches, were used to establish the effect of dependent variables on performance. The three branches of philosophies namely ontology, epistemology and axiology, which are the methodological rationalism approaches brought in the philosophical alignment. The target population was composed of 175 employees and the sample size was 60 employees. Questionnaire wasused as a research instrumentto gather the necessary data for the study. Mean and standard deviations were used to find out the extent of agreement by respondents and establish if the results could be trusted and generalised. The findings revealed that promotion and advancement, job security, recognition, relationship with management and being involved in decision making played significance roles in the performance of employees. Salary and wage adjustments were also important to reduce labour turnover. The findings revealed that the relationship of motivation and performance of employees proved to be positive basing on the dependent variables researched on. This included motivation, training, resources, work environment, performance management and leadership styles. It was recommended that management adjust their way of operations to improve performance of employees.